Antioxidant screening of Garcinia forbesii originated from Sabah - Suraya Abdul Sani; Mohammad Khalizan Sabullah; Wan Fahmi Wan Mohamad Nazarie; Ainol Azifa Mohd Faik; Rahmath Abdulla (Faculty of Science and Natural Resources, 2021)
Garcinia forbesii is a wild-type of plant that have been long used traditionally with broad utilities in several fields like medicines, cosmetics, food and neutraceutics. Increasing awareness towards the use of phytochemicals and other plant derives products worldwide has broaden the study of bioactivities from several industrial sectors. Therefore, the present study aims to screen the antioxidant and antimicrobial properties of fruits and leaves of Garcinia forbesii. The methanolic, hexanic and ethyl acetate extracts were obtained by maceration extraction, isolated and undergoes purification through Thin layer Chromatography (TLC) and Column Chromatography (CC). The highest yield of extraction are both from methanol extracts of fruits and leaves which are 9.26 ± 0.34 g and 7.04 ±0.21 g. The antimicrobial activity of the extracts was determined against Escherichia coli using Kirby-Bauer method. The disc diffusion assay showed that the inhibition of growth of E. coli was fully attributed to hexanic extract for fruits and leaves of G. forbesii while all other extracts displayed minimum or none inhibition zone. The inhibition zone of hexanic extract of leaves (11.83mm ± 1.04) showed the highest than fruits (9.33mm ± 1.53) among all the fractions. Antioxidant activities of the leave extracts of G. forbesii in reducing power, FRAP (ferric reducing antioxidant power) and DPPH followed the same order of methanolic > ethyl acetate > hexanic. Meanwhile, extract hexane, methanol and ethyl acetate of the fruits of G. forbesii showed IC50 values at 1.05%, 3.35% and 4.44% while for leaves are at 1.19%, 2.4% and 8.94% respectively. Methanol is therefore a better solvent to extract most of the antioxidant components from G. forbesii leaves.